Pengembangan Media Wayang Zootopia untuk Meningkatkan Keterampilan Menyimak Anak Usia Dini - Fatimah, Siti; Wahyudin, Erik (Diksi: Jurnal Pendidikan dan Literasi, 2025)
This study aims to develop and test the effectiveness of Zootopia Wayang media in improving the listening skills of 5-6-year-old children at Al Misbah Kindergarten. Listening skills are an important foundation in language development, but many children still experience difficulties due to the lack of interesting learning media. This study used the R&D model with the ADDIE approach. The media was developed using animal characters made of plywood, painted with bright colours, and equipped with a safe moving stick. The results of expert validation showed that this media was very feasible to use (average feasibility >84%). The effectiveness test with a one-group pretest-posttest design on 20 children showed an increase in the average score from 20.35 to 34.05. The results of the Wilcoxon test showed a significant difference (p = 0.000), with an N-Gain of 0.7003 (high category). In conclusion, Zootopia Wayang media is effective and feasible to use as a learning innovation to improve the listening skills of early childhood